Effect of electrodes on rubber insulating glove: article / Mohd Arif Safiuddin Mohd Noor - Mohd Noor, Mohd Arif Safiuddin (Universiti Teknologi MARA (UiTM), 2013)
This paper presents experimental procedures and data for comparative evaluation of the insulation value of the protective rubber insulation glove. This paper focused on the usage of Class 2 gloves. The objective of this research is to observe and analyze the characteristic of the rubber glove when it is given potential from different source of contact. The different electrodes used in this research were compared with each other in order to observe the breakdown voltage and also the tan 8. Experimental results for various types of electrode tested were analyzed. Collected results indicates that, different type of electrodes will yield different results of withstand levels for the gloves including the breakdown voltage and dielectric properties. This research only covers the experimental setup of normal test vessel due to the absence of the oil bath vessel. Hence the effects of corona and flashover have to be considered. This lead to conclusion that electrical performance of rubber glove will achieve breakdown voltage faster when it is in contact with flat circular electrode.